Prevalence and Risk Factors of Type II Diabetes Mellitus in Indonesia - Siti Ghadira Inayah Taslim; Shibli; Syafruddin A. R. Lelosutan (INDOGENIUS, 2026)
Background & Objective: Type II diabetes mellitus is a metabolic disorder caused by impaired insulin secretion or function and has become a global health problem. The number of people with type II diabetes mellitus worldwide is estimated to reach 537 million and is projected to increase to 783 million by 2045. In Indonesia, the prevalence among people aged ≥15 years is around 3 percent, with the main risk factors being obesity, hypertension, low physical activity, and high sugar consumption. This literature review aims to describe the prevalence and risk factors of type II diabetes mellitus in Indonesia. Method: This study is a literature review using Google Scholar and PubMed to search for publications from 2015 to 2025. The articles reviewed discuss the prevalence, risk factors, and distribution of type II diabetes mellitus based on sociodemographic characteristics. Result: The results of the study show that the prevalence of type II diabetes mellitus increases with age, especially in the >55 age group, ranging from 6.3 to 12.5 percent. The prevalence in women (±9.6 percent) was higher than in men (±6.9 percent). The dominant risk factors included obesity (OR 2.3–2.7), hypertension (OR 1.9–2.0), low physical activity, advanced age, and high sugar consumption. Conclusion: The prevalence of type II diabetes mellitus in Indonesia shows an increasing trend during the 2015–2025 period with relatively consistent risk factors. Prevention efforts need to focus on controlling risk factors through the promotion of a healthy lifestyle.